The polar code for patterning: how polarity and the cytoskeleton orchestrate asymmetric cell division during plant development - Garhewal, Akanksha; Angres, Gabriel J.; Muroyama, Andrew (Frontiers in Cell and Developmental Biology, 2025)
Cell polarity is fundamental to morphogenesis across living organisms. In plants, a dynamic interplay between polarity cues and the cytoskeleton orchestrates essential asymmetric cell divisions across diverse species. Here, we focus on three functions for the cytoskeleton—organelle positioning, cell growth and mitosis—and discuss our current understanding of how polarity controls these processes. By taking a comparative approach that highlights what is known about these pathways across plant species, we spotlight both the broadly conserved and cell type-specific ways that polarity can regulate division orientation. Because there have been significant developments in the field within the last several years, we focus our attention on recent work and give our perspective on exciting future avenues of investigation into the reciprocal relationship between polarity and the cytoskeleton.